Assessment of Community-Based Tourism Potential and Inventory in Ikot Ekpene Senatorial District, Akwa Ibom State - Augustine Michael Imikan; Nsisong Christopher Ekong; Malachy Ugochuckwu Okoroji (Randwick International of Social Science Journal, 2022)
The study aimed to carryout inventory and maps the distribution of community-based tourism attractions in Ikot Ekpene Senatorial District of Akwa Ibom State. The study was descriptive in nature and adopted purposive sampling method to select ten (10) communities for the study. The communities were drawn at least one from each of the Local Government Areas. Data for the study were obtained through questionnaire forms, interviews, focus group discussions and personal observations. The questionnaire forms were administered to a total of four hundred (400) respondents who were randomly selected among the ten (10) selected communities. The result of the study shows that community-based tourism potential are decaying in the local community due to ignorance of the local communities on tourism benefits and lack of involvement and participation in community-based tourism activities. However, new tourism potential /attractions were discovered during the inventory. We concluded that community-based tourism if well managed and restructured is a functional tool to driving sustainable tourism development. Therefore, it is recommended that the local communities should effectively participate and be involved in community-based related activities and they should be integrated in decision-making and management in the tourism industry to aid the sustainability of tourism development in the district.